Organizational Structure, Channels and Methods of Propaganda Work of the Soviet Military Administration in Germany, 1945–1949 - Roman Yu. Boldyrev; Jörg Morré (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2019)
Introduction. The paper deals with the issues of the propaganda system in the Soviet Occupation Zone in Germany (SOZ) between 1945 and 1949. Based on de-classified documents from Russian Archives propaganda organization, channels and methods of propaganda units of the Soviet Military Administration in Germany (SMAG) became a subject to study. The authors emphasize on control means towards German mass media and implementing the Soviet propaganda monopoly in East Germany.